2023
DOI: 10.18240/ijo.2023.10.11
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of antimicrobial peptides in human fungal keratitis

Jia-Song Wang,
Zhao Zhao,
Chao Wang
et al.

Abstract: AIM: To analyze a series of antimicrobial peptides (AMPs) in corneal tissue from individuals with fungal keratitis (FK) during the active phase of the fungus infection and after healing. METHODS: Patients undergone lamellar keratoplasty for the treatment of severe FK or corneal scar had their corneal buttons sampled. Quantitative real-time polymerase chain reaction (PCR) was used to ascertain the gene expression of human beta-defensin (HBD)-1, -2, -3, -9, S100A7, 8, 9, and LL-37. RESULTS: All AMPs’ messenger r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In addition, on the ocular surface, there are a large number of substances with antiinflammatory and bactericidal effects, such as secretory IgA, mucin glycoproteins, and antimicrobial peptides, such as human β-defensin 2 (HBD-2) and LL-37 (cathelicidin), which have been found to be particularly elevated in filamentous fungal keratitis [24,25]. Wang et al recently suggested that these antimicrobial peptides may not be equally expressed in fungal keratitis since they found HBD-2 mRNAs to be more elevated in Fusarium keratitis while LL-37 mRNAs in cases of Aspergillus keratitis [17].…”
Section: Immune Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, on the ocular surface, there are a large number of substances with antiinflammatory and bactericidal effects, such as secretory IgA, mucin glycoproteins, and antimicrobial peptides, such as human β-defensin 2 (HBD-2) and LL-37 (cathelicidin), which have been found to be particularly elevated in filamentous fungal keratitis [24,25]. Wang et al recently suggested that these antimicrobial peptides may not be equally expressed in fungal keratitis since they found HBD-2 mRNAs to be more elevated in Fusarium keratitis while LL-37 mRNAs in cases of Aspergillus keratitis [17].…”
Section: Immune Mechanismsmentioning
confidence: 99%
“…The cornea is therefore a natural barrier that prevents pathogens from further invading its stroma. Furthermore, the expression of antimicrobial peptides (AMPs), such as human β-defensin (HBD) and LL-37 (cathelicidin protein) by the epithelium, also contributes to this [17,18]. Moreover, the constant flow of tears can naturally clean the corneal surface from microorganisms and other substances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation